2016
DOI: 10.1016/j.biocel.2016.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the structural biology of the 26S proteasome

Abstract: There is growing appreciation for the fundamental role of structural dynamics in the function of macromolecules. In particular, the 26S proteasome, responsible for selective protein degradation in an ATP dependent manner, exhibits dynamic conformational changes that enable substrate processing. Recent cryo-electron microscopy (cryo-EM) work has revealed the conformational dynamics of the 26S proteasome and established the function of the different conformational states. Technological advances such as direct el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 53 publications
2
29
0
Order By: Relevance
“…Comparisons of Rpn11 active-site accessibility in the proteasome between different conformational states also revealed that the active site is occluded in the resting state of the proteasome but moves to a position over the ATPase outer-ring channel upon proteasome engagement with substrate[4,91,144]. This allows placement of the bond between the substrate and ubiquitin chain into the unobstructed Rpn11 active site as the substrate is threading through the ATPase pore, leading to amputation of the ubiquitin chain and continued substrate translocation.…”
Section: The Rp Lidmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparisons of Rpn11 active-site accessibility in the proteasome between different conformational states also revealed that the active site is occluded in the resting state of the proteasome but moves to a position over the ATPase outer-ring channel upon proteasome engagement with substrate[4,91,144]. This allows placement of the bond between the substrate and ubiquitin chain into the unobstructed Rpn11 active site as the substrate is threading through the ATPase pore, leading to amputation of the ubiquitin chain and continued substrate translocation.…”
Section: The Rp Lidmentioning
confidence: 99%
“…In the lid, the horseshoe-like structure formed by the winged-helix domains of the six PCI proteins cradles the MPN core of Rpn8/Rpn11 (Figures 7, 8a) [4,88,91,133,144]. The lid undergoes substantial conformational changes upon formation of the 26S proteasome, where it is splayed onto side of the Rpt3/Rpt6 base sector and makes contact with the CP as well[125].…”
Section: The Rp Lidmentioning
confidence: 99%
See 1 more Smart Citation
“…38,45,4749 The RPs contain receptors for ubiquitin recognition and will subsequently deubiquitinate, unfold, and transfer the substrate protein into the CP following ATP hydrolysis, as it proceeds through at least three major distinct conformational stages. 50,51 The degradation of ubiquitinated proteins requires one (19S–20S) or two regulatory particles (19S–20S–19S) to be docked onto the CP. 38,52 Not all additional modules require ATP hydrolysis to activate the 20S CP.…”
mentioning
confidence: 99%
“…During the dynamic process of (i) substrate accepting, (ii) commitment, and (iii) translocation three hypothetic conformational states of the yeast proteasome were distinguished by single particle cryo EM analysis (Figure 1) (Lander et al, 2013; Unverdorben et al, 2014). The translocation state might be dissected into more intermediates, since human proteasomes exist in at least four states during substrate processing (Wehmer and Sakata, 2016). …”
Section: Substrate Recognition By Poly-ubiquitylationmentioning
confidence: 99%